PERANCANGAN VPS DAN MULTI-REGION LOAD BALANCER UNTUK WEBSITE PT SCHLEMMER AUTOMOTIVE INDONESIA MENGGUNAKAN LAYANAN GOOGLE CLOUD PLATFORM - Grevalby; Elanda, Anggi; Suhada, Karya (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
PT Schlemmer Automotive Indonesia as a multinational company under the Schlemmer Group requires a website that can be accessed smoothly by users from various countries, such as Indonesia, Germany and China. In order for the website to be accessed quickly and stably in each of these countries, a reliable and efficient infrastructure is required. This study aims to design a VPS system and load balancer for the PT Schlemmer Automotive Indonesia website that can divide the traffic load between several servers or VPS instances and direct traffic to access servers that are in the closest location to the user. The method used in this study is the prototyping method with the stages of system requirements analysis, system design, system testing, and implementation. The test results show that the designed system can run well and proves that the use of VPS and load balancers can improve website performance and stability when traffic spikes occur. In conclusion, this study shows that the use of VPS and load balancers on the PT Schlemmer Automotive Indonesia website using the Google Cloud Platform service results in good website performance when accessed in each country.